Transforming member development through AI: A case study of training, coaching, mentoring, and duplication in network marketing ecosystem - Sitinjak, Manuntun; Irawan, Agustinus Purna; Handoyo, Sarwo Edy; Purwanto, Edi (Edelweiss Applied Science and Technology, 2025)
This study investigates how artificial intelligence (AI) can optimize the digital transformation of member development in a multi-level marketing (MLM) ecosystem. Focusing on the implementation of ChatGPT and Meta AI, the research explores their roles in supporting training, coaching, mentoring, and duplication processes. Using a qualitative case study design, data were obtained through semi-structured interviews, structured observations, and document analysis within Miora, an Indonesian MLM organization adopting AI-based learning support. The findings indicate that AI improves access to consistent knowledge, accelerates learning readiness, strengthens mentoring quality, and enhances duplication across geographically dispersed teams. Key challenges include differences in digital literacy, early user resistance, and the ongoing need to align technological assistance with human leadership. The study concludes that AI does not replace leaders but amplifies their capacity to guide and develop members more effectively. Practical implications highlight strategies for integrating AI into training ecosystems and designing scalable, AI-assisted development frameworks.